Why we need to talk about lifelong learning and intercultural universities (UCL Press, 2019)
This article explores whether and how contemporary discourses in lifelong learning (LLL) can support intercultural universities in Latin America. Since the late twentieth century, LLL has primarily been seen through a Eurocentric lens, with a strong focus on the development of skills for knowledge-based economies and societies. As this discourse has been promoted and adopted by so-called developing countries, the focus has shifted from an identified need for continuous learning in a global society to mainly targeting the promotion of basic education, as is evidenced by the United Nations Sustainable Development Goals. In this context, we have identified a need for further discussion and research on intercultural universities, many of which are becoming increasingly vulnerable in current neoliberal times. This article looks at two intercultural universities in Mexico and Ecuador and suggests that a more indigenized approach to LLL could provide a stronger sense of ownership and participation in decision-making. Thus, LLL can be an ally for a new and decolonized conceptual framework that further legitimizes intercultural universities and provides a long-term strategy for the future.